2020
DOI: 10.1186/s12991-020-00287-2
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated relationship between salivary oxytocin levels and attention to social information in adolescents and adults with autism spectrum disorder: a comparative study

Abstract: Background: Previous research studies have assessed the relationship between attention to social information and peripheral (e.g., plasma and salivary) oxytocin (OT) levels in typically developing (TD) children and children with autism spectrum disorder (ASD). A relationship between them was observed in TD children, but not in children with ASD. However, this relationship remains unexamined in other age groups. To clarify whether this lack of association is maintained throughout development in individuals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…Three investigated groups of adults [ 30 , 31 , 32 ]. Pertaining to sex, eight studies reported on exclusively male populations [ 4 , 5 , 7 , 8 , 32 , 35 , 37 , 38 ] and one study adopted an exclusively female sample [ 32 ]. For the studies involving a mixed population, four studies reported separate outcomes of OT level measurement for male and female subgroups and were entered accordingly in the subgroup analyses [ 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three investigated groups of adults [ 30 , 31 , 32 ]. Pertaining to sex, eight studies reported on exclusively male populations [ 4 , 5 , 7 , 8 , 32 , 35 , 37 , 38 ] and one study adopted an exclusively female sample [ 32 ]. For the studies involving a mixed population, four studies reported separate outcomes of OT level measurement for male and female subgroups and were entered accordingly in the subgroup analyses [ 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gazefinder, a system in which a set of devices to capture eye gaze patterns and stimulating movie clips are equipped in a personal computer (PC) with a 19-inch monitor (1280 × 1024 pixels), manufactured by JVC Kenwood Co. Ltd. (Yokohama, Japan), was chosen to measure eye gaze patterns. The technical features of this system have been described in previous studies ( 18 , 19 , 27 , 28 ). In brief, corneal reflection techniques enable the device to calculate eye gaze positions on the PC monitor as (X, Y) coordinates in pixel units, at a frequency of 50 Hz (i.e., 3,000 eye gaze positions detected per minute).…”
Section: Methodsmentioning
confidence: 99%
“…ADOS is a standard diagnosis tool for ASD but recently has been increasingly adopted as a primary outcome in ASD-related trials [ 24 , 27 , 31 35 ]. (ii) Gaze fixation time on socially relevant regions = changes in the percentage of gaze fixation time on the eye region of a talking face presented on a video monitor, between baseline and 6-week endpoint (endpoint − baseline), which were measured with Gazefinder, a validated all-in-one eye-tracking system, for a few minutes subsequent to the ADOS sessions using the standardized and validated method described details in elsewhere [ 18 , 24 , 36 , 37 ](JVC KENWOOD Corporation, Yokohama, Japan). (iii, iv, v, and vi) log-PDF mode of quantified facial expression production of a neutral face during 0–6, 0–2, 2–4, and 4–6 weeks = changes in the natural logarithm of the mode of the probability density function of neutral facial expression intensity during a semistructured situation conducted during a few minutes of social interaction in the “ Cartoons ” activity in ADOS module 4.…”
Section: Methodsmentioning
confidence: 99%